Measuring the Factor of the Criminal Action of Corruption (Case Study of Criminal Acts of Corruption in the Environment of Legislative Authority) - Gunawan, Tri Agus; Hakim, Sholihatul (Universitas Negeri Semarang (UNNES), 2019)
With the spirit of reform, it gives extraordinary power and authority to legislative members in line with their duties and functions based on the mandate of the constitution such as the functions of legislation, budgetary functions, and supervisory functions. With the current power and authority of legislative members, they often do not fully carry out the people's mandate, but injure the people's mandate with the capture of several legislative members in the vortex of corruption cases. This study attempts to analyze these causes that make corruption continue to occur in the legislative power environment while providing solutions that are fundamentally changes in our constitutional system This study uses normative legal research methods by examining primary legal materials, namely relevant laws and regulations and secondary legal materials in the form of library studies and also by utilizing quantitative data. The purpose of this study is to examine the fundamental factors causing the widespread of corruption cases that ensnare the legislative members when various regulations and criminal sanctions have often been imposed on convicted corruption before and do not have deterrent effects. The hypothesis that is temporarily built is that the authority/duties of legislative members, the high salary received now and also the policy of raising criminal sanctions are not effective in tackling corruption and this is the focus of the study in this study.